Efeito da Privação e da Restrição de sono sobre a densidade de receptores de andrógeno e de glicocorticóide no músculo esquelético - Venancio, Daniel Paulino [UNIFESP] (2010)
Aim: To investigate the effect of paradoxical sleep deprivation for 96 hours and sleep restriction for 21 days on the expression of glucocorticoid and androgens receptors in skeletal muscle gastrocnemius. Methods: Male rats of 3 months of age were distributed into 6 groups: experimental (control, deprived of sleep for 96 hours and paradoxical sleep rebound for 24 h, sleep restriction for 21 days, deprived of sleep for 96 hours treated with testosterone and paradoxical sleep-deprived treated with saline). The protocols submitted to sleep deprivation for 96 hours and sleep restriction for 21 days was the modified multiple platform method. At the end of this period, the animals were sacrificed and blood collected for testosterone and corticosterone measurement. The gastrocnemius muscle was dissected and processed for histology and immunohistochemistry, respectively and western blotting for receptor glucocorticoids. Results: Decrease of receptor immunoreactivity glucocorticoid and androgen receptor was not altered with periods of sleep deprivation study. We also observed that the sleep deprivation animals showed reduced cross section skeletal muscle. Furthermore, we observed reduced concentrations of testosterone and increased corticosterone concentration in all periods of sleep deprivation study. Conclusion: Paradoxical sleep deprivation for 96 hours and sleep restriction for 21 days led to subsensibilização of the glucocorticoid receptor and reduced muscle mass, causing atrophy of the gastrocnemius muscle.